Kinerja Anggota Komisi Ii Bidang Perekonomian Dan Keuangan Dewan Perwakilan Rakyat Daerah (DPRD) Provinsi Kepulauan Riau - Azwan Ar; Oksep Adhayanto (Jurnal Selat, 2013)
For the implementation of the duties and functions of the Regional Representatives Council (DPRD) Riau Archipelago Province efficiently and effectively, to be supported by the availability of fittings Council, one of which is the formation of working committees. Concerns regarding the performance of Commission II Economic Affairs and Finance House of Representatives (DPRD) Riau Islands province, such as the ability to understand the material substance of legislation drawn up based on the analysis aspect of philosophical, juridical and sociological, and skill knowledge in the field of legal-drafting, the mastery of the basic principles accounting, performance budgeting, budget preparation techniques and benefits. Formulation of the problem addressed in this research that the performance of members of the Commission II How the economy and financial Sector Legislative Council (DPRD) Riau Archipelago Province. As well as what factors are inhibiting performance improvement II Committee member for Economic Affairs and Finance Islands Provincial Parliament. The research method used is descriptive qualitative research, which is the process of organizing and sorting data into patterns and categories as well as the basic outline of the unit, so it can be stated theme as suggested by the data. The results were quite good performance of members of the Commission II of the economy and financial Regional Representatives Council (DPRD) Riau Archipelago Province. The results, the researchers concluded that the performance of the members of the Commission II of the economy and financial Regional Representatives Council (DPRD) Riau Archipelago Province in the execution of their duties, both in the legislative function, budget and oversight functions showed fairly good condition. Factors inhibiting performance of members of the Board of Commission II, such as the quality of human resources member of the Commission II for economy and finance DPRD Riau Archipelago Province less, disciplinary board members are still low, the lack of implementation of punishmant to members of the Board who are not performing their duties and the number of members of the Commission II are not comparable in their respective sectors. Key Word : performance, of the Commission II and DPRD.